View of microchip electrophoresis for clinical application in proteome analysis - Nakamura, Kazuyuki; Tabuchi, Mari; Kuramitsu, Yasuhiro; Baba, Yoshinobu (SEIBUTSU BUTSURI KAGAKU, 2004)
High-throughput with high quality proteome analysis is necessary for proteomics research and medical diagnosis. In this paper, we introduce the view of advanced microchip electrophoresis for clinical application in proteomics research. Protein size separation based on sodium dodecyl sulfate-gel electrophoresis (SDS-GE) requires denaturing, but we propose that denaturing is unnecessary for analysis by microchip electrophoresis. We attained dramatically improved sensitivity without compromising size determination by omitting the protein denaturing process. Protein expression of Jurkat cells during stress-shock induced apoptosis was readily analyzed using this system. We found that a food extraction effectively induced apoptosis of Jurkat cells. This system will accelerate the proteomics research and will be utilize for the medical diagnosis in future.